PROJECTION OF THE 7Li WAVE FUNCTION IN THE {(dn)α}- AND{(αd)n}-MODELS ON THE 6Li{αd}+ n CLUSTER CHANNEL - Afanasyeva, N.V.; Burkova, N.A.; Zhaksybekova, K.A.; Urazalin, A.A. (Recent Contributions to Physics, 2011)
Within the three-body α dn -model for 7Li nucleus the Li + n relative-motion wave functions have been obtained and spectroscopic Sn -factors of neutron separation has been calculated.